Toward a Radical Model of Social Work in Rural Communities. Issue 1 (2nd January 2017) - Vance, Carter
ABSTRACT: "Rural" areas as distinct from "urban" continue to be defined by greater personal interactions and less emphasis on formal systems of support. This reality rests in contradiction to the overwhelming majority of social work scholarship and theory development which takes place in an urban context. As such the present-day act of being a "social worker" in a rural community can, in many ways, feel like a bad fit, back-applying the model of an urban generalist into an environment whose organic community ties the social work model itself was originally designed to substitute for. In recognition of this, it is necessary to develop a "combined" model of practice for social work with rural communities and peoples. The fundamental distinction to be made is that rural social work, in its most radical form, is less concerned with adapting persons to the Gesellschaft than it is with strengthening the capacity of the Gemeinschaft to provide the kind of support capacity it historically has, taking into account changes and challenges resulting from factors such as globalization, urban sprawl, and cultural change.